2023
DOI: 10.3390/v15051072
|View full text |Cite
|
Sign up to set email alerts
|

The Intersection of COVID-19 and Metabolic-Associated Fatty Liver Disease: An Overview of the Current Evidence

Abstract: The global population is currently experiencing the impact of the SARS-CoV-2 coronavirus, which has caused the Coronavirus Disease 2019 (COVID-19) pandemic. With our profound comprehension of COVID-19, encompassing the involvement sequence of the respiratory tract, gastrointestinal system, and cardiovascular apparatus, the multiorgan symptoms of this infectious disease have been discerned. Metabolic-associated fatty liver disease (MAFLD), formerly known as non-alcoholic fatty liver disease (NAFLD), is a pervas… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 187 publications
0
7
0
Order By: Relevance
“…T2DM can also influence the immune system, potentially affecting the host response to COVID-19 [ 38 ]. The interaction between T2DM, MAFLD, and the immune response to COVID-19 may lead to nuanced and interconnected effects that are difficult to disentangle [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…T2DM can also influence the immune system, potentially affecting the host response to COVID-19 [ 38 ]. The interaction between T2DM, MAFLD, and the immune response to COVID-19 may lead to nuanced and interconnected effects that are difficult to disentangle [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…Existing hepatic steatosis and MAFLD have been identified as influencers of COVID-19 disease severity, Intensive Care Unit (ICU) admission rates, and the necessity for invasive mechanical ventilation. Conversely, COVID-19 contributes to the exacerbation of hepatic injury and the progression of disease severity in MAFLD and other liver disorders [ 14 ]. However, it is essential to acknowledge that MAFLD frequently coexists with additional entities such as obesity and DM within the broader spectrum of metabolic syndrome.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While the relationship remains contentious, initial reports during the COVID-19 pandemic suggested that patients with MAFLD may face an elevated risk of experiencing a more severe disease course [ 35 , 36 , 37 , 38 , 39 , 40 ]. However, it remains unclear whether MAFLD merely associates with adverse outcomes or whether it plays a causal role [ 41 ]. Furthermore, it is crucial not only to acknowledge the potential impact of MAFLD on the course of COVID-19 but also to recognize the effects of the COVID-19 pandemic itself on patients with MAFLD and the overall epidemiology of the disease [ 41 , 42 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, it remains unclear whether MAFLD merely associates with adverse outcomes or whether it plays a causal role [ 41 ]. Furthermore, it is crucial not only to acknowledge the potential impact of MAFLD on the course of COVID-19 but also to recognize the effects of the COVID-19 pandemic itself on patients with MAFLD and the overall epidemiology of the disease [ 41 , 42 ].…”
Section: Introductionmentioning
confidence: 99%